Entropy generation between two vertical cylinders in the presence of MHD flow subjected to constant wall temperature - Mahian, Omid; Öztop, Hakan Fehmi; Pop, Ioan; Mahmud, Shohel; Wongwises, Somchai (Pergamon-Elsevier Science Ltd, 2013)
An analytical solution is presented on the entropy generation due to mixed convection between two isothermal cylinders where a transverse magnetic field is applied to the system. The governing equations in cylindrical co-ordinates are simplified and solved to obtain the distribution of entropy generation and the effects of MHD flow on it. The results for the entropy generation number (N-S), the Bejan number (Be) and average entropy generation number (N-S,N-ave) are presented for different values of the Hartmann numbers, radius ratios and a flow parameter, Gr/Re. The results show that the entropy generation decreases with increases in the magnetic field. In addition, it is found that with decreases in the radius ratio, the effects of MHD flow on the entropy generation are reduced. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Entropy generation; MHD flow; Isothermal annulus; Mixed convection